Utility of basic hematological indices in early detection of hemoglobinopathies in paediatric population of southern India. - VM, Hemanth Kumar; K, Pushpalatha; S, Srinivasamurthy (Journal of Pathology of Nepal, 2023)
Background: Cases diagnosed as Microcytic Hypochromic Anaemia in paediatric age group will be subjected to basic hematological indices and further confirmed in cases of high suspicion through Hemoglobin Electrophoresis and High-Performance Liquid Chromatography. This study aimed to identify simple indices and cost-effective methods to detect undiagnosed cases of thalassemia syndromes being treated for nutritional deficiency anemias.Materials and Methods: The study included 100 pediatric patients, from a period of January 2019 to June 2020. Case selection was based on children whose hemoglobin levels were below the cutoff value according to age. They were further subjected to Sehgal and Mentzer indices and suggestive cases were subjected to Gel Electrophoresis (Both Alkaline and Acid) and High-Performance Liquid Chromatography.Results: 43% of the cases showing abnormality on screening hematological indices were further subcategorized on gel electrophoresis and confirmed on HPLC. 27% of the cases were diagnosed to be β Thalassemia Trait, which constituted the most frequent type of hemoglobinopathy detected. There were 8% of the cases diagnosed to be as Sickle Cell disease which included major and minor forms. 5% of the study cases were diagnosed as β Thalassemia major. 3% of the cases were diagnosed as HbE disease, HbE trait and ȣβ Thalassemia. Conclusions: Hematological indices can be used effectively for early detection of suspected cases of hemoglobinopathies.